Pulsed Magnetic Field Resonance Therapy - Ebner, Erich (British Journal of Healthcare and Medical Research, 2025)
Medical-therapeutic and especially alternative procedures are increasingly developing in parallel with subspecialized high-performance medicine and are increasingly losing the understanding and advantages of integrative therapy. However, a look at the basic prerequisites of life toward physical laws reveals a different picture. A picture that questions this development of an isolated subspecialization. Magnetism, as a fundamental physical force, is the basis of life and thus one of the decisive forces in the origin and development of all life on Earth, as well as in all biological processes, chemical, biochemical, and physiological processes. It will be shown how the effect of magnetism, in its manifestation of diamagnetism, develops and affects biological molecules. Pulsed magnetic field resonance therapy therefore offers itself as an adjuvant therapy option.